John Dewey and the paradox of liberal reform - Paringer, William Andrew, 1948- (SUNY series, global conflict and peace education., 1990)
This book provides a fresh critique of John Dewey and the progressive tradition and warns against the superficial renaissance of Deweyan philosophy present in many of today's modern liberal educational reform movements. Challenging the four pillars of Dewey's pragmatism--science, nature, democracy, experience--Paringer argues for a critical or radical education praxis that more sensitively comes to grips with the difficulties of teh nuclearized, postmodern world.